The Applicability of Micro Learning Based on Historical Perspective - Hasan Hasan; Dedi Kuswandi; Zahid Zufar At Thaariq; Hutkemri Zulnaidi (Graduate School of Universitas Negeri Malang, 2022)
The focus on learner-centred learning approaches is a concern which needs to be facilitated as a matter of study. Microlearning has evolved in facilitating learners in short learning activities as viewed through history. This paper aims to review the application of microlearning historically. This narrative study uses deconstruction techniques with a historical research approach consisting of (1) heuristics, (2) verification, (3) interpretation, and (4) historiography. The study found that microlearning is a development of the concepts of microteaching and microcontent. This paper can be used as a reference in the development of microlearning as research and learning in the future.